2015
DOI: 10.1002/hep.27544
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to vigorous physical activity volume is an important factor for managing nonalcoholic fatty liver disease: A retrospective study

Abstract: Recently, the beneficial effects of increased physical activity (PA) on nonalcoholic fatty liver disease (NAFLD) in obese subjects were reported. However, the optimal strength and volume of PA in lifestyle modification to improve NAFLD pathophysiology and be recommended as an appropriate management of this condition are unclear. The primary goal of this retrospective study was to estimate the beneficial effects of a varying volume of moderate to vigorous intensity PA (MVPA) on the improvement of NAFLD. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 37 publications
3
107
0
Order By: Relevance
“…The present study demonstrated that inactive patients physically active obtained biochemical markers (LDL and glycemia) a hepatic transaminases and alkaline phosphatase in relation to the physically active ones, which can imply in a worse hepatic condition. In the insufficiently active group we can observe that the values found in the active group can be justified because the individuals in this age group are very involved with domestic and work activities that demand a higher level of intensity to be performed, even with some physiological decompensation within the menstrual cycle [16] among women, generating a significant calcium loss over the years [17]; however, because they are more physically active, they possibly present a lower burden of osteoarticular damage in relation to physically inactive women.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that inactive patients physically active obtained biochemical markers (LDL and glycemia) a hepatic transaminases and alkaline phosphatase in relation to the physically active ones, which can imply in a worse hepatic condition. In the insufficiently active group we can observe that the values found in the active group can be justified because the individuals in this age group are very involved with domestic and work activities that demand a higher level of intensity to be performed, even with some physiological decompensation within the menstrual cycle [16] among women, generating a significant calcium loss over the years [17]; however, because they are more physically active, they possibly present a lower burden of osteoarticular damage in relation to physically inactive women.…”
Section: Discussionmentioning
confidence: 99%
“…46,57 The volume of exercise is an important factor and it has been shown that 250 minutes of weekly exercise was more effective than 150 minutes. 61 Besides aerobic training, resistance training (which improves muscle strength through repetitive weight-based exercises), also improves NAFLD. 62,63 A combination of aerobic training and resistance training may give the maximum benefit though further studies are required to confirm the same.…”
Section: Anti-obesity Drugsmentioning
confidence: 99%
“…It is recommended to perform exercises for at least 250 minutes per week. 8 In general, 5 to 10% reduction in body weight in obese or overweight people over 6 to 12 months has been advocated through changes to eating habits and the practice of physical activity. This recommendation is based on short-term studies that showed an improvement in IR and in liver histology with gradual weight loss, as shown in Table 1.…”
Section: Treatment Of Nafldmentioning
confidence: 99%